MONEY-MAKING PLATFORM BUSINESS THROUGH VIDEO SNACK APPLICATION IN PERSPECTIVE AKAD JU'ALĀH - Jelita (JURISTA: Jurnal Hukum dan Keadilan, 2021)
Snack Video application is called a money-making application because this application provides income for creators and ordinary users. Several differences of opinion arise in response to this phenomenon regarding the validity and permissibility of the money earned from the Snack Video application. Based on the concept of contracts in Islam, the income earned from the Snack Video application is included in the ju'alāh contract, which is offering a job that is not clear that the recipient of the job can complete and he is entitled to a reward if he successfully completes it. The purpose of the research is to find out the acquisition of money in the money-making platform business through the Snack Video application and to find out the money-making platform business through the Snack Video application in the perspective of the ju'alāh contract. This research uses normative legal research with conceptual and theoretical approaches. In the business practice of the money-making platform through the Snack Video application, namely income as a content creator through the creator reward programme as a form of appreciation for the achievements and contributions of creators. And income as an ordinary user, rewards for users who successfully complete missions/tasks that have been provided on the Snack Video task page. Secondly, the business of the money-making platform through the Snack Video app is permissible as long as the contract attached to the Snack Video app is in accordance with the pillars and conditions of the ju'alāh contract. Downloading and installing the Snack Video app to earn money is not something that is forbidden.